Efficient Optical Trapping of Nano-Particle via Waveguide-Coupled Hybrid Plasmonic Nano-Taper - Yi-Chang Lin; Po-Tsung Lee (IEEE Photonics Journal, 2019)
For manipulating nano-bio-specimens, we propose a tweezing device by integrating a triangular-shaped photonic-plasmonic nano-taper on top of a coupling waveguide. The device can exert strong trapping force on nano-particle owing to efficient optical energy usage and accessible field distribution. Working principle and optical characteristics of the device are fully investigated and discussed. The optimized device shows an excellent trapping capability with low threshold power of 3.57 mW for stable trapping n 100 nm polystyrene particle. Simple geometry and high tolerance to pattern misalignment between trap unit and coupling waveguide are beneficial for realistic fabrication. Furthermore, the footprint of trap unit is only 400 nm × 625 nm. We believe this design will be very useful to the development of lab-on-a-chip system.